HUMAN RIGHTS CONTENT OF MODERN DIGITAL STRATEGY OF THE EUROPEAN UNION - Natalia V. Bocharova; Oleksander M. Bykov (Alfred Nobel University Journal of Law)
The article is devoted to the study of the process of development of methodological approaches to legal regulation in the field of information and informatization in the EU, with emphasis on the provision of human rights in the conditions of the information society and the definition of vectors of democratic development. The focus is on the content of the newest document in this area, the European Declaration on Digital Rights and Principles, signed by the leadership of the European Union in December 2022. On the basis of the analysis of the "digitized" legislative framework of the EU, it was found that the idea of balancing technological development with respect for ethical principles and the promotion of human rights is held as a fundamental one. Already with the beginning of the spread of information and communication technologies, the original methodological guideline for the EU leadership became the thesis that the person, his needs and interests are at the center of social transformations that accompany the construction of an information society. The human rights approach to digitization processes was demonstrated in a number of documents of the so-called European digital agenda. The conceptual principles of the general approach to building the legal framework of the information society in the EU include three areas of action: 1) technologies that work for people, 2) a fair and competitive digital economy, 3) an open, democratic and sustainable society. Within the third strand, it is defined: it aims to ensure that EU values and ethical rules are applied both online and offline. The human-centered approach formed in the EU should be taken into account in Ukraine on the way to European integration when creating national legislation on the legal regulation of the Internet environment and the development of social policy in the conditions of the dominance of information technologies.